Expression analysis of tissue factor pathway inhibitors TFPI-1 and TFPI-2 in Paralichthys olivaceus and antibacterial and anticancer activity of derived peptides - Guanghua Wang; Bing Xie; Yanli Su; Qinqin Gu; Dongfang Hao; Hongmei Liu; Changbiao Wang; Yonghua Hu; Min Zhang (Veterinary Research, 2021)
Abstract Tissue factor pathway inhibitors (TFPI), including TFPI-1 and TFPI-2, are Kunitz-type serine protease inhibitors that mainly inhibit the blood coagulation induced by tissue factors. Previous reports on teleost proved TFPI play important roles in innate immunity. In this study, two TFPI (PoTFPI-1 and PoTFPI-2) molecules from Japanese flounder (Paralichthys olivaceus) were analyzed and characterized for their expression patterns, antibacterial and anticancer activities of the C-terminal derived peptides. Quantitative real time RT-PCR analysis shows that constitutive PoTFPI-1 expression occurred, in increasing order, in the brain, muscle, spleen, gills, head kidney, blood, intestine, heart, and liver; PoTFPI-2 was expressed, in increasing order, in the brain, gills, head kidney, muscle, intestine, spleen, liver, heart, and blood. Under the stimulation of fish pathogens, both PoTFPI-1 and PoTFPI-2 expressions increased significantly in a manner that depended on the pathogens, tissue type, and infection stage. Furthermore, C-terminal peptides TP25 and TP26, derived from PoTFPI-1 and PoTFPI-2, respectively, were synthesized and proved to be active against Micrococcus luteus (for TP25 and TP26) and Staphylococcus aureus (for TP25) via retardation effects on bacterial nucleic acids. In addition, TP25 and TP26 also displayed significant inhibitory effects on human colon cancer cell line HT-29. These results reveal that both PoTFPI-1 and PoTFPI-2 play important roles in host innate immunity. The antibacterial activity and anticancer cells function of TP25 and TP26 will add new insights into the roles of teleost TFPI.